Indonesia Carbon Credit Trading: Economic Opportunity or Environmental Liability? - Rahmatullah, Indra (Hasanuddin University, 2025)
On the 26th of September 2023, the 7th President of Indonesia, Joko Widodo, officially inaugurated the launch of the first carbon credit trading platform of Indonesia, IDXCarbon. The launch of this carbon credit trading has marked another stepping stone of Indonesia to its commitment to combating climate change and further strengthening its position in the global environmental conservation arena. The aim of this article is to critically evaluate the potential opportunities and benefits of the carbon trading scheme in Indonesia through the lens of Environmental Economics theory, while also assessing the potential challenges through the scope of Political Ecology theory . This article employs Environmental Economics theory in analyzing how the establishment of a carbon trading market presents potential benefits in addressing greenhouse gas emissions by implementing economic value in carbon reductions. The carbon trading adoption in the environmental policy framework in Indonesia aims to encourage low-carbon economic practices and innovations across various sectors. On the contrary, this article will also provide a critical examination towards the adoption of carbon trading in Indonesia through the lens of Political Ecology theory. Political Ecology theory will highlight the underlying power relations across state, private actors, local communities, and international stakeholders that raise skepticism regarding the credibility, governance, and the actual environmental impact of the carbon trading scheme in Indonesia. Furthermore, Political Ecology theory focuses on the potential challenges, such as fair implementation and preventing the marginalization of vulnerable communities involved in carbon trading practices. Overall, the establishment of a carbon trading market in Indonesia through IDXCarbon marked a revolutionary step in Indonesia’s commitment to combat climate change. Through the comparative analysis of the potential opportunities and challenges in regards to the adaptation of carbon trading in Indonesia, this article argue that the adaptation of carbon trading in Indonesia requires a robust regulatory and environmental ethical framework in order to balance the potential benefits presented by the framework while mitigating the potential challenges that can further hinder the overall benefits of carbon trading.